Integrative Mapping of Factors and Dynamics of Work-Life Balance in Flexible and Remote Work Arrangements: Systematic Review - Ryalno Stefano Noya (Westscience Press, 2026)
This study aims to map the factors shaping and influencing the dynamics of work-life balance in flexible and remote work arrangements, as well as to identify research trends, theoretical perspectives, and existing research gaps in the literature. The study employed a Systematic Literature Review (SLR) approach using the PRISMA procedure through the Scopus database. From an initial 120 identified articles, 31 articles met the inclusion criteria and were selected for the final synthesis. The findings indicate that work-life balance is influenced by psychological, organizational, social, technological, and individual factors. The results also reveal paradoxical dynamics, where flexible work arrangements can improve autonomy and well-being while simultaneously increasing stress, burnout, role conflict, and blurred boundaries between work and personal life. The study concludes that work-life balance is the result of interactions among multiple factors within the modern work environment.